(untitled) (Conferencea, 2022)
According to Article 13 of the Constitution of the Republic of Uzbekistan, democracy in the Republic of Uzbekistan is based on universal principles, according to which a person, his life, his freedom, his dignity and other inalienable rights are recognized as the highest value. The direct protection of democratic rights and freedoms by the c and laws is the constitutional and legal basis for the application of coercive measures of criminal procedure